2010
DOI: 10.1056/nejmoa0908993
|View full text |Cite
|
Sign up to set email alerts
|

CPR with Chest Compression Alone or with Rescue Breathing

Abstract: Dispatcher instruction consisting of chest compression alone did not increase the survival rate overall, although there was a trend toward better outcomes in key clinical subgroups. The results support a strategy for CPR performed by laypersons that emphasizes chest compression and minimizes the role of rescue breathing. (Funded in part by the Laerdal Foundation for Acute Medicine and the Medic One Foundation; ClinicalTrials.gov number, NCT00219687.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
161
1
9

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(173 citation statements)
references
References 29 publications
2
161
1
9
Order By: Relevance
“…In one study, there was a trend, although not statistically significant, toward increased rates of survival to hospital discharge with hands-only CPR in the subgroups with a cardiac cause of OHCA (15.5% vs 12.3%, P 5 .09) and with a shockable rhythm (31.9% vs 25.7%, P 5 .09). 39 Another study reported a slightly more positive trend to hospital discharge (19.1% vs 14.7%, P 5 .16) but no change in 30-day mortality (8.7% vs 7.0%, P 5 .26). 40 With no apparent harm and possible benefit in providing hands-only CPR instructions, recently released American Heart Association guidelines call for compression-only CPR in the initial management of cardiac arrest.…”
Section: Out-of-hospital Cardiac Arrestmentioning
confidence: 90%
“…In one study, there was a trend, although not statistically significant, toward increased rates of survival to hospital discharge with hands-only CPR in the subgroups with a cardiac cause of OHCA (15.5% vs 12.3%, P 5 .09) and with a shockable rhythm (31.9% vs 25.7%, P 5 .09). 39 Another study reported a slightly more positive trend to hospital discharge (19.1% vs 14.7%, P 5 .16) but no change in 30-day mortality (8.7% vs 7.0%, P 5 .26). 40 With no apparent harm and possible benefit in providing hands-only CPR instructions, recently released American Heart Association guidelines call for compression-only CPR in the initial management of cardiac arrest.…”
Section: Out-of-hospital Cardiac Arrestmentioning
confidence: 90%
“…It is essential to warn the bystanders about providing an appropriate chest compression alone approach and its optimal long-term survival benefit [2]. The results of some randomized trials did not support the superiority of chest compression alone on compression plus rescue breathing [11,12]. A meta-analysis of these randomized trials restricted to those patients with a cardiac pathogenesis suggested a short-term survival benefit of chest compression alone [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…20 Untrained laypersons are now instructed to begin compression-only CPR because a number of studies have demonstrated bystander compression-only CPR to be equivalent to conventional bystander CPR. 7,21,22 The algorithm is now simplified, as shown in Figure 1. Two randomized trials demonstrated no benefit for conventional CPR over compression-only CPR, and a meta-analysis suggested that bystander compression-only CPR was superior to bystander conventional CPR.…”
Section: Bystander Cprmentioning
confidence: 99%